PENGARUH MORALITAS INDIVIDU, PENEGAKAN HUKUM, KEADILAN DISTRIBUTIF, KEADILAN PROSEDURAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI DENGAN PERILAKU TIDAK ETIS SEBAGAI VARIABEL INTERVENING (Studi pada Satuan Kerja Perangkat Daerah Kabupaten Kampar ) - Diyah Fitri Yulianti; Emrinaldi Nur DP; Rofika ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The tendency of accounting fraud has grown in many countries, including in Indonesia. The purpose of this study is to analyze the direct effect of individual morality, law enforcement, distributive justice and procedural justice to tendency of accounting fraud and indirect effect of individual morality, law enforcement, distributive justice and procedural justice to tendency of accounting fraud with unethical behavior as intervening variable. Samples in this study are 18 departements in Kampar with 64 respondents. The data were analyzed by using PLS analysis technique (Partial Least Square). The result shows that individual morality and distributive justice have direct influence toward tendency of accounting fraud. But, law enforcement and procedural justice do not have influence toward tendency of accounting fraud. The result for indirect effect show that law enforcement, distributive justice and procedural justice have significant influence to tendency of accounting fraud through unethical behavior. But, individual morality does not have significant influence to tendency of accounting fraud through unethical behavior.Keywords: tendency of accounting fraud, unethical behavior and PLS (Partial Least Square)